Children’s names founded with the words «son» and «daughter» in central asian turkish people (Journal of Philosophy Culture and Political Science, 2024)
The study deals with children’s names created by using the words son and daughter in the names given to children in the Turkish people of Central Asia.In the society we live in, one of the most important goals of parents in the family is to have a child. One of the most important duties of parents who have children towards a child is to give their child a beautiful name.Throughout the historical process experienced by the Turkish nation, various name-giving traditions have emerged due to different reasons experienced by parents. The names given according to these traditions reflect the history, geography, beliefs, social structure, and cultural characteristics of the society.According to the findings we made in field researches, the conditions in families in Central Asian Turkish communities before the birth of the child, the unexpected developments that occur during the birth of the child and the events that occur after birth play a great role in naming the child.The names formed with the words «son» and «daughter,» which are frequently found in the names given to children in Central Asian Turks, are often seen to be directly related to the desire to have a boy. Today, especially in Kazakhs and Kyrgyz, the third of three daughters born in the family in succession i usually given names formed with the word «ul/son.» For example, names such as «Ulbolsun», «Ulbolgan», «Uljalgas», «Ulergen» directly reveal the desire for a boy, while names such as «Kıztumas», «Kızdıkoy» express more harshly and clearly that the girls of the family have enough and now want boys.In the study, the reasons for the words son and daughter in the names given to children, especially in Central Asian Turkish people, are emphasized and the subject is examined thoroughly.Key words: tradition, naming, son, girl, boy, gender